Synthesis of a One-Dimensional Coordination Polymer of Nickel(II) Complex with a β-Oxodithioester Ligand - Ricardo Rosas-Reyes; Yasmi Reyes-Ortega; T. Jesus Morales-Juarez; Virginia Gómez-Vidales; Ivan García-Orozco (Journal of Chemistry)
Bis-[methyl-1-hydroxy-1-cyclopentene-2-dithiocarboxylate-O,S]nickel(II) 1 was prepared starting from methyl 2-hydroxycyclopent-1-encarbodithioate ligand (CPDT) and Ni(II), and catena-[(μ2-4,4′-Bipyril)-bis-(methyl-2-hydroxy-1-cyclopentene-2-dithiocarboxylate-O,S)]nickel(ΙΙ) 2 was prepared in good yields from 1 plus 4,4′-bipyridyl (bpy) by shish-kebab methodology. The structure of 1 was confirmed by FTIR, elemental analysis, 1H NMR, UV–vis in chloroform solution and in solid, XPS, and PXRD. Compound 2 was characterized by FTIR, elemental analysis, UV–vis in chloroform solution, and in solid, XPS, PXRD, ESR, and solid state magnetization measurements. The structure of the polymer was established mostly by PXRD, ESR, and magnetization.